Epitaxial formation of Ni germanide on Ge(0 0 1) substrate by reactive deposition. (August 2015) - Deng, Yunsheng; Nakatsuka, Osamu; Suzuki, Akihiro; Sakashita, Mitsuo; Zaima, Shigeaki
Abstract: We investigated the crystalline structure of a NiGe layer grown on Ge(0 0 1) substrate through the reactive deposition method. NiGe layers grown at 350 °C are a single crystalline, provided that they are thin enough—below 22 nm. The epitaxial relationship with the Ge(0 0 1) substrate is then as follows: NiGe(1 1 1)//Ge(0 0 1), and NiGe[0 1 ¯ 1]//Ge[1 1 0]. However, the NiGe layer becomes polycrystalline when the thickness reaches 22 nm or thicker. We proposed a two-step deposition method combined with solid-phase reaction to suppress the polycrystalline formation and successfully achieved an epitaxial NiGe layer over 22 nm-thick with an atomically flat interface. We also clarified that the Ge atom is the dominant diffusion species during the reactive deposition and that the Ni atom dominates during the solid-phase reaction.